The serum uric acid/high-density lipoprotein cholesterol ratio: a novel predictor for the presence of abdominal aortic aneurysm - Li, Wei; Luo, Songyuan; Lin, Wenhui; Hu, Xiaolu; Zhou, Dan; Xu, Wenmin; Zhou, Yingling; Luo, Jianfang; Feng, Yingqing (Frontiers in Cardiovascular Medicine, 2024)
ObjectiveRobust evidence has demonstrated that inflammation plays an important role in the occurrence and development of abdominal aortic aneurysms (AAA). The serum uric acid (UA)/high-density lipoprotein cholesterol (HDL-C) ratio (UHR) has recently been recognized as a new biomarker for evaluating inflammatory and anti-inflammatory interactions. However, whether UHR is associated with AAA remains unclear. This study aimed to explore the association between UHR and presence of AAA.MethodsWe prospectively performed a hospital-based and community-based AAA screening program using ultrasonography in 9,064 individuals at Guangdong Provincial People’s Hospital and two communities in China. Logistic regression analysis was used to explore the association between UHR and presence of AAA. In addition, the restricted cubic spline (RCS) regression method was used to visually investigate the dose-response relationship between UHR and the presence of AAA. Propensity score matching (PSM) analysis was conducted to adjust for baseline variations and diminish selection bias, and subgroup analysis was performed to investigate the consistency of the conclusions.ResultsThe prevalence of AAA was 2.45% (222/9,064) in the present study. The optimal cut-off value of UHR was 17.0%, which was selected according to the receiver operator characteristic curve. The prevalence of AAA was 3.96% in the high-UHR group (UHR ≥ 17%) and 1.54% in the low-UHR group (UHR < 17%) (P < 0.001). After adjusting for other relevant clinical covariates, UHR was independently associated with the presence of AAA, either as a continuous variable (odds ratio [OR] 1.03, 95% confidence intervals [CI] 1.01–1.05, P < 0.001) or as a categorical variable (OR 1.63, 95% CI 1.18–2.26, P = 0.003). The RCS curve showed a nonlinear dose-response relationship between UHR and the presence of AAA. Moreover, the positive correlation between UHR and the presence of AAA remained significant after PSM and subgroup analyses.ConclusionsUHR was positively associated with the presence of AAA, and there was a non-linear dose-response relationship between them. Thus, UHR may serve as a novel and reliable predictor of AAA.